2012
DOI: 10.3390/membranes2030395
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Molecular-Level Mechanism of Membrane Degradation in the Polymer Electrolyte Fuel Cell

Abstract: Chemical degradation of perfluorosulfonic acid (PFSA) membrane is one of the most serious problems for stable and long-term operations of the polymer electrolyte fuel cell (PEFC). The chemical degradation is caused by the chemical reaction between the PFSA membrane and chemical species such as free radicals. Although chemical degradation of the PFSA membrane has been studied by various experimental techniques, the mechanism of chemical degradation relies much on speculations from ex-situ observations. Recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 144 publications
(155 reference statements)
0
26
0
Order By: Relevance
“…Polymer electrolyte fuel cells (PEFCs) have been widely investigated as technologies for the transportation sector [1][2][3][4][5][6], portable power generation [5], and residential co-generation systems [1,3,4,6] because of their environmentally friendly operation [1,3,4,6], modularity [4], and high energy conversion efficiency [1,2,5,6]. However, some long-standing issues remain, including the high cost of platinum (Pt), unreliable performance, and poor durability, which are major impediments to largescale commercialization of the PEFC [1,2,4,5,[7][8][9][10]. Pt and Pt-based alloys are generally the most used catalysts for PEFC because Pt exhibits the highest catalytic activity for the oxygen reduction reaction (ORR), chemical stability, high exchange current density, and superior work function [10].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer electrolyte fuel cells (PEFCs) have been widely investigated as technologies for the transportation sector [1][2][3][4][5][6], portable power generation [5], and residential co-generation systems [1,3,4,6] because of their environmentally friendly operation [1,3,4,6], modularity [4], and high energy conversion efficiency [1,2,5,6]. However, some long-standing issues remain, including the high cost of platinum (Pt), unreliable performance, and poor durability, which are major impediments to largescale commercialization of the PEFC [1,2,4,5,[7][8][9][10]. Pt and Pt-based alloys are generally the most used catalysts for PEFC because Pt exhibits the highest catalytic activity for the oxygen reduction reaction (ORR), chemical stability, high exchange current density, and superior work function [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is also found that the identified two major degradation pathways from the side chain, i.e., ether bond cleavage at the deprotonated state and sulfo-unzipping pathway at the protonated state, can also be seen in the Nafion-like side chain [2,5]. far, counter measure for sulfo-unzipping pathway has been proposed [11].…”
Section: Polymer Degradation In Polymer Electrolyte Fuel Cellmentioning
confidence: 93%
“…The degradation of polymer electrolyte by OH radical in polymer electrolyte fuel cell (PEFC) is one of the crucial issues to be solved for higher durability of the cell [2][3][4][5][6]. While the unzipping mechanism from -COOH at the main chain terminal is well-known as degradation pathways of perfluorinated sulfonic acid (PFSA) polymer, another degradation pathway of polymer electrolyte was pointed out [7].…”
Section: Polymer Degradation In Polymer Electrolyte Fuel Cellmentioning
confidence: 99%
“…These reactions result in shorting main chains and consequently in loss of the equivalent weight of the polymer. Other studies [21,48,49] have proved a degradation of the side chains corresponding to reactions (9)e (11). In this case, hydroxyl radicals attack CeO bonds in the ether groups of the side chains.…”
Section: Membrane Thickness and Conductivitymentioning
confidence: 98%
“…At the last decade, numerous degradation models have been published [19e43]. Most of the models consider degradation phenomena in a single component of the fuel cell: either in the membrane [21,25,28,29], or in the catalyst layer [20,23,24,26,27,30], or in the gas diffusion layer [22]. There are much less models predicting durability [19,34,35,40e44] or performance [25,33e39] of a complete fuel cell or stack.…”
Section: Introductionmentioning
confidence: 99%